Boosting energy harvesting performance in (Ba, Ca)(Ti, Zr)O3 lead-free perovskites through artificial control of intermediate grain size. Issue 28 (14th June 2018) - Yan, Xiaodong; Zheng, Mupeng; Sun, Shengjun; Zhu, Mankang; Hou, Yudong
Abstract : In this study, (Ba0.85 Ca0.15 )(Ti0.9 Zr0.1 )O3 (BCTZ) lead-free ceramics with enhanced energy density were prepared by two-step sintering. Abstract : In this study, (Ba0.85 Ca0.15 )(Ti0.9 Zr0.1 )O3 (BCTZ) lead-free ceramics with enhanced energy density were prepared by two-step sintering. All ceramics fall into the rhombohedral–orthorhombic–tetragonal (R–O–T) phase boundary near room temperature, and a dense microstructure with an intermediate grain size was observed. The enhanced piezoelectric and energy harvesting properties were attained over a wide grain size range of 10–15 μm, benefiting from the construction of the R–O–T phase boundary. Most interestingly, the maximum values of d 33 and d 33 × g 33 (530 pC N −1 and 9720 × 10 −15 m 2 N −1 ) can be achieved at 1500/1350 °C with a grain size of 13.7 μm. The interpretation of the underlying mechanism related to domain and defect engineering has been investigated systematically. Furthermore, a high output power of 99 μW and an energy conversion efficiency of 10% were obtained at a simple cantilever energy harvester fabricated from a 1500/1350 °C specimen under an acceleration of 1.0 g, making the current system very promising for piezoelectric energy harvesting applications.